DNAR-06. LOSS OF HISTONE H3 THREONINE 45 PHOSPHORYLATION DECREASES H3K36ME3 TO ABROGATE THE RADIATION-INDUCED DNA DAMAGE IN GLIOBLASTOMA MULTIFORME. (14th November 2022) - Parwani, Kiran; Spangle, Jennifer; McSwain, Leon; Javadi, Ramona Haji Seyed; Kenney, Anna; Yu, David
Abstract: Glioblastoma multiforme (GBM) is the most common and fatal adult brain tumour. As radioresistance is a common occurrence and contributes to poor patient prognosis, exploiting the mechanistic basis of GBM radioresistance to develop new therapeutic approaches remains an unmet clinical need. Chromatin post-translational modifications (PTMs) can augment cancer radioresistance. Several chromatin PTMs are regulated by PI3K/AKT, which is frequently hyperactivated in GBM. Previous research demonstrated that the PI3K effector AKT phosphorylates histone H3 at threonine 45 (pH3T45) in response to DNA damage. To genetically dissect the function of H3T45 phosphorylation in the DNA damage response, we engineered the PI3K pathway-activated U87MG GBM cell line to stably overexpress wildtype H3, or a phospho-null H3T45A mutant. We show that in both the presence and absence of irradiation, cells harbouring the phospho-null H3T45A mutant decreases H3K36me3 on free and nucleosome-incorporated histones, which may suggest a deficiency in DNA repair protein recruitment. By surveying irradiation-induced 53BP1 foci formation, we demonstrate that loss of pH3T45 compromises damage repair through NHEJ by delaying the onset of repair signaling. We also observe a defect in DNA damage resolution, which enhances apoptosis to reduce cell clonogenicity and proliferative capacity. Irradiation does not further reduce clonogenicity and proliferation in the phospho-null H3T45A-expressing cells. Taken together, these data suggest a critical function for PI3K-directed H3T45 phosphorylation in DNA damage repair and that loss of pH3T45 may contribute to GBM radioresistance. We anticipate that further characterization of this phosphorylation event will inform the understanding of GBM radioresistance and may suggest novel therapeutic strategies.